Immune‐Mediated Sensorineural Hearing Loss in the Pediatric Population. (13th July 2021) - Gorthey, Scott; Patel, Ravi; Vambutas, Andrea
Abstract : A case series with chart review of pediatric patients with immune‐mediated sensorineural hearing loss, including sudden sensorineural hearing loss and autoimmune‐mediated hearing loss, was performed. Ninety‐eight patients with sensorineural hearing loss were reviewed, and 41 patients met the inclusion criteria, which included corticosteroid therapy for a decline in sensorineural hearing. The primary outcome was the corticosteroid response rate: 61% of patients responded. The secondary outcome was a sustained response following multiple courses of corticosteroids for additional hearing loss, which correlated with timely corticosteroid treatment: 57% showed sustained response with multiple treatments, but as anticipated, patients were more likely to respond when treated promptly. Sustained responses fell over time with multiple treatments. These data demonstrate pediatric immune‐mediated sensorineural hearing loss is corticosteroid responsive in at a rate similar to their adult counterparts and should be considered for similar treatment approaches.